Походження печерної затворництва на Русі в історико-географічному вимірі - Кабанець, Є. (Інститут історії України НАН України, 2007)
У статті досліджено витоки печерного затворництва на теренах Давньої Русі на тлі загального розвитку Православної церкви у Близькосхідному та Середземноморському регіонах. Проаналізовано походження практики затвірництва на Русі, його організаційної та ідеологічної структури. The article is investigated the sources of Old Russian monastic organization on a background development of the Universal orthodox church in the Near-Eastern and Mediterranean region. It is given the estimation of all varieties and categories of monastic estate in his historical evolution. The work is analyzed the origin of Ancient Rus’ solitary practice, his organizational and ideological structure in the context of borrowing and mastering of doctrine of isichazm.